Teacher talk of praises in English classroom interaction - Aulia Rahmani; Asnawi Muslem; Bukhari Daud (English Education Journal, 2021)
This study was conducted at International Elementary School of Bunga Matahari to find out the type of teacher talk in English classroom interactions and the students’ responses on teacher talk of praises. The descriptive qualitative design was applied and aimed to analyze the types of talk employed by the teacher in the classroom interaction based on FIACSystem presented by Flanders (1970). The data were analyzed using an interaction model of Miles, Huberman, and Saldana (2013) et al. and focused on the teacher and student talk in ICP class. This research employed observation through video recording in order to reach the objectives of this study. The participant in this study were 45 students with 15 students in each class and 3 English teachers. The results showed that by analyzing responses of transcription from the observation, the teacher talk of giving praises is approximately less, giving direction dominates the teacher talk category that consists of direct influence of teacher talk. In addition, the students’ response was dominantly toward teacher talk of praises.